Climate litigation before the European Court of Human Rights: some observations on the case Klimaseniorinnen and Others v Switzerland - Liguori, Anna (Diritto Pubblico Europeo - Rassegna online, 2023)
On 29 March 2023 the first public hearing concerning climate change-related violations of human rights was held before the Grand Chamber of the European Court of Human Rights on the case Klimaseniorinnen and Others v Switzerland. The applicants are the association Klimaseniorinnen and four elderly ladies who, after exhausting domestic remedies, turned to the European Court on 26 November 2020 alleging inter alia a violation of Articles 2 (right to life) and 8 (protection of private and family life) ECHR due to Switzerland’s failure to take appropriate measures to reduce the risks for their health and lives connected to climate change. In this paper the author focuses on two aspects which were at the centre of the hearing before the Grand Chamber, namely the notion of victim and the applicability of Articles 2 and 8 ECHR - more specifically, of the positive obligations inherent in these articles - in the light of the commitments undertaken by States under international climate law. Some final considerations address an important question which is relevant both in respect to the status of victim and the merits of the case, i.e. the collective causation problem